Synthesis, structural characterization and evaluation of sol-gel-based NF-TiO2 films with visible light-photoactivation for the removal of microcystin-LR - Pelaez, M.; P. Falaras; V. Likodimos; A. G. Kontos; de la Cruz, A.A.; O'Shea, K.; Dionysiou, D.D. (Applied Catalysis B: Environmental, 2010)
This study reports on the synthesis, characterization and environmental application of immobilized nitrogen and fluorine co-doped TiO2 (NF-TiO2) photocatalyst. A fluorosurfactant-based sol-gel approach was employed to enhance the physicochemical properties and photocatalytic activity of NF-TiO2 under visible and UV light for the degradation of the hepatotoxin microcystin-LR (MC-LR). The films were characterized by XRD, environmental scanning electron microscope (ESEM), TEM, AFM, EPR, micro-Raman, X-ray photoelectron spectroscope (XPS), UV-vis spectroscopy and porosimeter analysis. The results revealed that by modifying the molar ratio of the fluorosurfactant, we could effectively control the physicochemical properties and obtain films with high BET surface area and porosity, small crystallite size and narrow pore size distribution. UV-vis spectroscopy showed an increase in the absorption capacity of NF-TiO2 in the visible light range compared to reference films. The existence of interstitial nitrogen and substitutional fluorine in the titanium dioxide (TiO2) lattice was determined by XPS. Comparative EPR measurements between the co-doped and reference samples identified distinct N spin species in NF-TiO2, with a high sensitivity to visible light irradiation. The abundance of these paramagnetic centers verifies the formation of localized intra-gap states in TiO2 and implies synergistic effects between fluorine and nitrogen dopants. Micro-Raman spectroscopy showed the growth of small amounts of brookite concomitantly with the major anatase TiO2 phase, which could promote the system's photocatalytic activity through the formation of anatase/brookite heterojunctions. Analysis of the lower frequency Eg anatase Raman mode indicated the occurrence of size effects reflecting phonon confinement in the anatase nanocrystallites as well as deviations from stoichiometry due to structural defects in the co-doped sample. NF-TiO2 films effectively degraded MC-LR under visible and UV light compared to reference film. Similar MC-LR degradation rates under visible light after three cycles revealed high mechanical stability and no irreversible changes of the film during photocatalysis. This process has the potential of providing environmentally benign routes for drinking water treatment with solar powered photocatalytic systems. © 2010 Elsevier B.V.